LOCAL WISDOM VALUES IN EFL ONLINE LEARNING: EMERGING ENVIRONTMENTAL ISSUES - Umar Al Faruq A. Hasyim; Nurul Puspita (Prodi Tadris Bahasa Inggris, 2021)
Abstract Local wisdom values mean society awareness about their ability in recognizing the surrounding condition. In this context, the values refer to the Lampungnese custom in planting crop. Unfortunately, many EFL learners were not familiar with their surroundings. Furthermore, this research describes the used of environmental issue topic in learning Essay writing. The teaching and learning process was done by EFL students by using online platform. It was suggested during the pandemic situation. However, the aim of this research is describing EFL students’ activities in emerging environmental topic toward their essay. This research was done on second semester of essay writing students. It was about 27 students. In conducting the teaching and learning process the lecturers choose any pictures that deal with the local culture of Lampungnese in planting crop as a topic. Then, the students would be more familiar with the values of the culture and elaborate the values in term of essay writing.